Effects of Vitamin D Use on Health-Related Quality of Life of Breast Cancer Patients in Early Survivorship. (February 2019) - Andersen, M. Robyn; Sweet, Erin; Hager, Shelly; Gaul, Marcia; Dowd, Fred; Standish, Leanna J.
Background: Vitamin D supplements may prevent recurrence, prolong survival, and improve mood for women with breast cancer, although evidence for these effects is preliminary.Methods: This report describes vitamin D supplement use by 553 breast cancer patient/survivors (193 who used a naturopathic oncology [NO] provider and 360 who did not) participating in a matched cohort study of breast cancer outcomes.Results: We found that more than half of breast cancer patients reported using vitamin D supplements. Women who received care from NO providers in early survivorship may be more likely to use vitamin D supplements ( P < .05). Approximately 30% of breast cancer patients with blood levels recorded in their medical chart were potentially vitamin D deficient (<30 ng/mL). Vitamin D supplement use at study enrollment was associated with higher levels of self-reported health-related quality of life (HRQOL) at enrollment ( P < .05) and predicted better HRQOL at 6-month follow-up ( P < .05). Sufficient blood levels of vitamin D recorded between enrollment and follow-up were also associated with better HRQOL at follow-up ( P < .05).Conclusions: Vitamin D supplementation by breast cancer patients is common both during and after treatment for breast cancer, but deficiency may also be common. NO and conventional providers may be able to promote vitamin D sufficiency through vitamin D supplementation and by encouraging healthy solar exposure. Further studies should be undertaken examining whether vitamin D supplementation and higher blood levels might improve HRQOL among women with breast cancer in early survivorship.